Uma análise crítica de gênero de vídeos online de popularização científica - Silva, Thales Cardoso da (2022)
Vídeos about Science “for all” can be seen as a discursive genre which is part of the process of science popularization, understood as an activity system permeated by different discursive genres (BAZERMAN, 2010). In the field of studies about discursive genres, the debate about the relation between technology and language has gained more and more space, mostly due to new communication possibilities associated to the internet. In this context, we consider relevant to study characteristics of online science videos for education as a genre in the process of science popularization, with special emphasis in strategies employed for recontextualizing (BERNSTEIN, [1990] 2003; CALSAMIGLIA; van DIJK, 2004; MOTTA-ROTH, 2009; LUZÓN, 2019) science knowledge to a new audience. Thus, the main objective of the present study is to analyze online videos of science popularization, published on YouTube, within the perspective of Critical Genre Analysis (MOTTA-ROTH, 2008; MOTTA-ROTH; HEBERLE, 2015). The corpus of the present study consists in 12 videos, published on YouTube, on the channels SciShow and TED-Ed. The methodological procedures are divided in two steps: the first consists in a documental analysis of the publication and production context, and, the second, in the linguistic multimodal analysis, which, in turn, consists in the analysis of the verbal semiotic component, by the categories of Informality (HYLAND, 2017) and Metadiscourse (HYLAND, 2005), and visual semiotic component, by means of the categories of Lexicogrammatical simplification (KRESS; van LEEUWEN, 2006; HENDGES; MARQUES, 2018) and Pedagogical function (DIMOPOULOS; KOULAIDIS; SKLAVENITI, 2003). Results indicate a context strongly influenced by the search of popularity and fidelity by the spectator, in an online platform aimed at generating revenue motivated by the number of accesses to a video. Linguistically, there is an informal and everyday tone in the reference to science, in a way of highlighting the relations among ideas presented, keeping the attention of the viewer, and referencing science as part of everyday life, by a direct and personal dialogue. Visually, the predominance in animation seems to be a form of representing science and scientific events in a ludic form in terms of essence, and not details. The recontextualization of scientific knowledge takes place, mostly, by means of vague reference to knowledge, without emphasis to the work and methodological commitment needed for the science process. Online science popularization videos can be seen as a genre with potential for the development of literacies, within which we highlight critical literacy (CERVETTI et al., 2001), scientific literacy (MOTTA-ROTH, 2011; PEARSON et. al., 2010) and multiliteracies (COPE; KALANTZIS, 2009).